Pengukuran Terhadap Nilai Perusahaan, Apakah Masih Penting? Studi Kasus pada Perusahaan Sektor Pertambangan Periode 2020-2023 - Annisa Aulya Hadi; Indah Kurniyawati (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
The study aims to examine the effect of good corporate governance, tax planning, and tax avoidance on firm value in mining companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2023. Thiis type of research is quantitative research and uses secondary data. The sample collection technique uses purposive sampling, obtained 24 companies for 4 years of observation (2020-2023), so that 96 samples will be used in this study. The analysis model used is multiple linear analysis. The result showed that the good corporate governance variable proxied by the board of commisioners has a negative influence on firm value, the tax avoidance variable has a positive effect, whlile the tax planning variable has no effect on firm value.